Implementation of Performance Assessment Policy Bayt Al-Hikmah Foundation Employees, Pasuruan City - Shomad, Abdul; Said, M. Mas’ud; Ahmadi, Rulam (Budapest International Research and Critics University, 2022)
This research uses a qualitative approach with a type of case study research. The data collection uses observation, interviews and documentation with purposeful sampling techniques. Meanwhile, the data analysis technique uses componential techniques. The results of this study are: First, finding standards used in the implementation of performance appraisal policies, namely: Punctuality Standards, Quality Standards, Quantity Standards, Behavior Standards, and Yield Standards. Second, Find the performance appraisal models used in the implementation of performance appraisal policies, namely: Chcklist Model, Graphic Scale Model, Concise Description Model, Management by Objective (MBO) Model and Mixed model (mixed), which combines several models as follows: check list model, concise description and graphical scale model. And third, find obstacles that occur in the implementation of performance appraisal policies, namely: Manual assessment system, equality of performance appraisal models, lack of socialization, the subjectivity of appraisers, and the absence of feedback from employees.